Process Mineralogy and Occurrence State of Lithium of Spodumene Tailings in Sichuan Province - Panpan WANG; Junfeng WU; Lin CHEN; Yanqing CHEN (Kuangchan zonghe liyong)
This is an article in the field of process mineralogy. The study objects are Lijiagou and Jiajika tailings, Sichuan Province. The samples were identified by optical microscopy, artificial heavy sand research (separation, identification, etc.), optical semi-quantitative analysis, chemical analysis, MLA automatic quantitative detection of minerals, LA-ICPMS in-situ analysis of mineral trace elements, and electron microscope energy spectrum analysis, X-ray powder crystal diffraction analysis and other work. The chemical mineral composition and lithium occurrence state of the tailings were studied. The results are as follows: 1. The Li2O grade of the tailings from Lijiagou and Jiajika is 0.44%～0.64%, both of which are near the boundary grade and can be re-enriched. The content of associated valuable elements such as niobium, tantalum, beryllium and rubidium does not meet the comprehensive recycling standard. 2. In the tailings from two different areas, the main material for reconcentration and recycling is spodumene and the associated trace useful minerals are mainly trace niobite-tantalite series minerals and beryl, while rubidium mainly exists in dispersed state in lithium Muscovite and potassium feldspar. 3. The main recovery target mineral of tailings is spodumene, the theoretical grade of Li2O in concentrate products is 7.33%, and the theoretical recovery rates of Lijiagou and Jiajika card concentrate are 86.14% and 87.87%, respectively. 4. The artificial heavy sand test of tailings shows that the content, distribution rate and yield of Li2O are high in the coarse grade, but low in the fine grade.